2022
DOI: 10.1017/s2045796022000464
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and psychosocial stressors have independent effects on the level of subclinical psychosis: findings from the multinational EU-GEI study

Abstract: Aims Gene x environment (G×E) interactions, i.e. genetic modulation of the sensitivity to environmental factors and/or environmental control of the gene expression, have not been reliably established regarding aetiology of psychotic disorders. Moreover, recent studies have shown associations between the polygenic risk scores for schizophrenia (PRS-SZ) and some risk factors of psychotic disorders, challenging the traditional gene v. environment dichotomy. In the present article, we studied the role of GxE … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 91 publications
0
6
0
Order By: Relevance
“…Environmental risks have also been found to act additively and synergistically with childhood trauma [87][88][89] and stressful life events 90,91 , contributing to the persistence of subthreshold psychosis symptoms in the general population. Psychosocial stressors such as childhood trauma and stressful life events have further been associated with higher levels of positive, negative, and depressive symptoms in the general population 92,93 . In addition, these psychosocial stressors, along with polygenic risk 65 Yes Yes Yes Hogdes et al 118 Yes n/a n/a Jang et al 131 Yes n/a n/a Mason et al 135 Yes n/a Yes Shim et al 125 Yes No n/a Wiesman van der Teen et al 64 No Yes n/a scores were found to exhibit independent additive effects on these three dimensions of subclinical psychosis 92,93 further supporting the stress-vulnerability hypothesis.…”
Section: Psychosocial Stressmentioning
confidence: 99%
See 2 more Smart Citations
“…Environmental risks have also been found to act additively and synergistically with childhood trauma [87][88][89] and stressful life events 90,91 , contributing to the persistence of subthreshold psychosis symptoms in the general population. Psychosocial stressors such as childhood trauma and stressful life events have further been associated with higher levels of positive, negative, and depressive symptoms in the general population 92,93 . In addition, these psychosocial stressors, along with polygenic risk 65 Yes Yes Yes Hogdes et al 118 Yes n/a n/a Jang et al 131 Yes n/a n/a Mason et al 135 Yes n/a Yes Shim et al 125 Yes No n/a Wiesman van der Teen et al 64 No Yes n/a scores were found to exhibit independent additive effects on these three dimensions of subclinical psychosis 92,93 further supporting the stress-vulnerability hypothesis.…”
Section: Psychosocial Stressmentioning
confidence: 99%
“…Psychosocial stressors such as childhood trauma and stressful life events have further been associated with higher levels of positive, negative, and depressive symptoms in the general population 92,93 . In addition, these psychosocial stressors, along with polygenic risk 65 Yes Yes Yes Hogdes et al 118 Yes n/a n/a Jang et al 131 Yes n/a n/a Mason et al 135 Yes n/a Yes Shim et al 125 Yes No n/a Wiesman van der Teen et al 64 No Yes n/a scores were found to exhibit independent additive effects on these three dimensions of subclinical psychosis 92,93 further supporting the stress-vulnerability hypothesis. However, it is important to note that no gene-environment interaction was found 93 .…”
Section: Psychosocial Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…However, current evidence suggest that G × E might not be the only process relevant for SZ risk. Other models like GE correlation (Warrier et al 2021), or even pure additive models with no interaction (Pignon et al 2022) might also drive the effects of childhood trauma or other sources of psychosocial stress on SZ risk.…”
Section: Interplay Between Genetic and Environmental Factors In Szmentioning
confidence: 99%
“…It is possible that such an abnormal response can occur after SARS-COV-2 infection, increasing the risk of rst-episode psychosis (FEP) [9]. Moreover, SARS-COV-2 infection -especially severe forms -represents a stressor and a negative life event, and could cause or trigger a psychotic disorder [10][11][12].…”
Section: Introductionmentioning
confidence: 99%